Prevalence of thyroid dysfunction in type 2 diabetes mellitus patients in Saharanpur, Uttar Pradesh, India. - Anil Kumar Garg; Virendra Singh Saini; Satyanand Sathi; Prabhat Agrawal; Atul Kumar; Prabhat Vats; Anurag Tomer; Shubhra Sharma; Jagmohan; Ashwarya Gupta; Dilli Raman Panhaur (Medico Research Chronicles, 2019)
As per World Health Organization (WHO) data - India, China and USA are among the top three countries with a high number of diabetic populations. In 2015 there were about 69.2 million patients (7.8%) affected with type 2 diabetes mellitus in India. Thyroid dysfunction was more common in type 2 diabetes mellitus subjects as compared to nondiabetics. Both diseases influence each other in several ways. Treatment of diabetic patient becomes very difficult when both thyroid disorder and diabetes mellitus exist together. Present study is designed to estimate the prevalence of thyroid dysfunction in type 2 diabetes mellitus subjects along with other biochemical parameters. Among the diabetic group 109 patients and 120 patients in control group were found to be euthyroid. Higher prevalence of thyroid dysfunction was found in patients with type 2 diabetes mellitus, 19.26% patients in Group I and 9.77% patients in Group II were found to have thyroid dysfunction. A routine assessment of thyroid function test should be performed for patients with type 2 diabetes mellitus.